A kind of anti-pollution flashover insulator and its preparation method

By using nanomolybdenum sulfide and nanotitanium dioxide to prepare functional additives, the problem of poor anti-fouling flash performance of existing porcelain insulators is solved, the water-repellent effect on the surface of the insulator is achieved, the flashover phenomenon is avoided, and the safe operation of the power grid is ensured.

CN119118635BActive Publication Date: 2025-04-29SHENZHEN YINXING INSULATOR ELECTRIFIED RAILWAY EQUIP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411593249.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-29
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing high-strength and impact-resistant porcelain insulators have poor anti-fouling flash performance, which is prone to deterioration of insulation performance and flashover due to fouling, affecting the safe operation of the power grid.

Method used

Functional additives are prepared using materials such as nanomolybdenum sulfide and nanotitanium dioxide. Through the hydrangea structure of nanomolybdenum sulfide and the cone-spiked structure of nanotitanium dioxide, a core-shell structure is formed. Combined with modifiers and azobisisohetene, functional additives with excellent hydrophobic properties are prepared and coated on the surface of the insulator to improve anti-fouling flash performance.

Benefits of technology

It significantly improves the anti-fouling flash performance of the insulator, reduces the possibility of filth accumulation on the surface of the insulator, avoids the occurrence of flashover, and thus ensures the safe operation of the power grid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of insulators, specifically to an anti-pollution flashover insulator and a preparation method thereof; the surface of the anti-pollution flashover insulator is coated with an anti-pollution flashover coating, and the anti-pollution flashover coating is composed of the following raw materials in parts by weight: 50 to 60 parts of epoxy resin, 7 to 10 parts of 4,4'-sulfonyl diphenylamine, 5 to 8 parts of nano magnesium hydroxide, 2 to 4 parts of nano zinc oxide, 2 to 5 parts of 1,3-cyclohexanedimethylamine, 3 to 5 parts of 1,4-butanediol diglycidyl ether and 4 to 6 parts of functional additives. The insulator prepared by the present invention has excellent anti-pollution flashover performance, effectively ensures its quality, and can also prevent the probability of large-scale pollution flashover accidents during power transmission to a certain extent, and ensure the safe operation of the power grid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulators, and in particular to an anti-pollution flashover insulator and a preparation method thereof. Background Art

[0002] Insulators are devices installed between conductors of different potentials or between conductors and ground potential components, which can withstand voltage and mechanical stress. As a special insulating control, insulators can play an important role in overhead transmission lines. In the early years, insulators were mostly used on telegraph poles, and gradually developed into high-type high-voltage wire connection towers with many disc-shaped insulators hung at one end to increase the creepage distance. They are usually made of glass or ceramic. Insulators can be divided into suspension insulators and pillar insulators according to different installation methods. According to the different insulating materials used, they can be divided into porcelain insulators, glass insulators and composite insulators (also called synthetic insulators). According to the different voltage levels used, they can be divided into low-voltage insulators and high-voltage insulators.

[0003] In the patent document with application number "CN201810909612.0", a high-strength, impact-resistant porcelain insulator and a preparation method thereof are provided, which belongs to the technical field of porcelain insulators. The high-strength, impact-resistant porcelain insulator includes a porcelain body and a glaze layer, which are respectively composed of a plurality of components. The preparation method of the high-strength, impact-resistant porcelain insulator includes the steps of double grinding, heating and softening, pressing into a blank, high-temperature glazing and slow cooling. Although the insulator prepared by this patent document has excellent impact resistance and can match the use requirements of ultra-high voltage power transmission. However, its anti-pollution flashover performance is relatively poor. Pollution flashover is caused by the decrease of insulation performance after the surface is polluted and damp, resulting in surface discharge, which further causes flashover. The flashover of the insulator will cause the feeder circuit breaker of the substation to trip and stop the power supply. Once a pollution flashover occurs in the insulator in operation, it will cause a large-scale, long-term sudden power outage, causing serious economic losses. Based on this, the present invention provides an anti-pollution flashover insulator and a preparation method thereof to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide an anti-pollution flashover insulator and a preparation method thereof. The prepared insulator has excellent anti-pollution flashover performance, which effectively ensures its quality and can also prevent the probability of large-scale pollution flashover accidents during power transmission to a certain extent, thereby ensuring the safe operation of the power grid.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing an anti-pollution flashover insulator, comprising the following steps:

[0007] Step 1, accurately weigh the following raw materials by weight: 50-55 parts of aluminum oxide, 20-30 parts of bauxite, 15-20 parts of clay, 6-10 parts of potassium feldspar, 3-6 parts of dolomite powder, 7-10 parts of bentonite, 15-25 parts of nano titanium dioxide, 4-6 parts of nano silicon nitride, 3-5 parts of sodium silicate and 2-3 parts of rare earth oxide; after weighing, store and set aside;

[0008] Step 2: Put the raw materials weighed in step 1 into a sand mill for sand milling to obtain blank particles with a diameter of 3 to 5 μm; store them for future use;

[0009] Step 3, sequentially subjecting the green sheet particles obtained in step 2 to ball milling, impurity removal, moisture control, drying, green sheet repairing, baking, glazing and sintering; after naturally cooling to room temperature, coating the surface with anti-pollution flashover coating, and obtaining the anti-pollution flashover insulator after drying.

[0010] Furthermore, the anti-pollution flashover coating is composed of the following raw materials in parts by weight: 50 to 60 parts of epoxy resin, 7 to 10 parts of 4,4'-sulfonyl diphenylamine, 5 to 8 parts of nano magnesium hydroxide, 2 to 4 parts of nano zinc oxide, 2 to 5 parts of 1,3-cyclohexanedimethylamine, 3 to 5 parts of 1,4-butanediol diglycidyl ether and 4 to 6 parts of functional additives.

[0011] Furthermore, the preparation method of the functional additive comprises the following steps:

[0012] The first step is to add acrylic acid and polyethylene glycol monomethyl ether into toluene at a molar ratio of 2 to 3:1, mix and stir evenly, then add hydroquinone with a mass of 1.5 to 2.0% of acrylic acid and p-toluenesulfonic acid with a mass of 3 to 4% of polyethylene glycol monomethyl ether in sequence, mix and stir evenly, and reflux for 8 to 12 hours; after the reaction is completed, remove toluene and unreacted monomers in the product components, and the final product is recorded as a modifier; wherein the mass of toluene is 5 to 8 times that of polyethylene glycol monomethyl ether, and the molecular weight of polyethylene glycol monomethyl ether is 1000;

[0013] Step 2: Disperse the inorganic carrier evenly in toluene at a solid-liquid ratio of 10 to 30 g / L, then add 3-(methacryloyloxy)propyltrimethoxysilane and hydroquinone in an amount of 0.8 to 1.2 times the mass of the inorganic carrier, respectively, and stir evenly, and stir the mixture at a temperature of 80 to 90° C. for 25 to 40 hours. After the reaction is completed, centrifuge, wash, and vacuum dry the resulting components in turn, and store the resulting solid material for later use.

[0014] The third step is to put the solid material into toluene at a solid-liquid ratio of 20-40 g / L, and then add a modifier with a mass of 0.3-0.5 times that of the solid material and 0.02-0.03 times that of azobisisoheptanenitrile. After mixing and stirring evenly, stir and react at a temperature of 90-95° C. for 8-10 hours. After the reaction is completed, centrifuge, wash and vacuum dry the product components in turn, and the final product is a functional additive.

[0015] Furthermore, the preparation method of the inorganic carrier is as follows: nano-molybdenum sulfide is uniformly dispersed in an ethanol aqueous solution with a concentration of 70-85wt% at a solid-liquid ratio of 5-10g / L, ammonia water is added and ultrasonically dispersed uniformly, and then magnetic stirring is performed at a temperature of 45-55°C for 2-3h, and then an ethanol solution of tetrabutyl titanate is slowly added to the obtained mixed components, and the mixture is kept warm for reaction at a temperature of 50-60°C for 3-5h; after the reaction is completed, the product components are centrifuged, and the obtained filter cake is washed 2-3 times with anhydrous ethanol and deionized water respectively, and then vacuum dried to obtain the inorganic carrier.

[0016] Furthermore, the preparation method of the nano molybdenum sulfide comprises the following steps: adding sodium molybdate and oxalic acid in an amount 0.4 to 0.6 times the mass of thioacetamide and 3 to 5 times the mass of thioacetamide respectively to a 2 to 5 wt % aqueous solution of thioacetamide, transferring the mixture into a reaction kettle after magnetic stirring for 20 to 30 minutes, and sealing and heat-insulating the mixture at a temperature of 180 to 220° C. for 20 to 25 hours; after the reaction is completed, naturally cooling the resulting components to room temperature, and then subjecting the components to solid-liquid separation, ultrasonically washing the filter cake with anhydrous ethanol and deionized water respectively until the upper solution is almost colorless, and then vacuum drying the resulting solid filter material at a temperature of 60 to 70° C., and finally rapidly annealing the mixture under argon protection to obtain nano molybdenum sulfide.

[0017] Furthermore, the rapid annealing temperature is 550-650° C., and the annealing time is 40-60 min.

[0018] Furthermore, the rare earth oxide is selected from any one of yttrium trioxide, lanthanum trioxide and samarium trioxide.

[0019] Furthermore, the concentration of the ammonia water is 25-28 wt %, and its usage is 5-10% of the volume of the ethanol aqueous solution.

[0020] Furthermore, the concentration of tetrabutyl titanate in the ethanol solution of tetrabutyl titanate is 0.08-0.12 mol / L, and its amount is 40-60% of the volume of the mixed components.

[0021] In a second aspect, the present invention provides an anti-pollution flashover insulator, which is manufactured using the above-mentioned preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention uses thioacetamide aqueous solution, sodium molybdate and oxalic acid as raw materials to prepare nano molybdenum sulfide with a hydrangea structure, then uniformly disperses the nano molybdenum sulfide in an ethanol aqueous solution, and sequentially adds ammonia water and an ethanol solution of tetrabutyl titanate, and deposits a dense nano titanium dioxide shell layer on the surface of the nano molybdenum sulfide after heat preservation reaction, and finally prepares an inorganic carrier with a core-shell structure and a cone-thorn structure formed by the deposition of nano titanium dioxide on the surface. The obtained inorganic carrier is uniformly dispersed in toluene, and 3-(methacryloyloxy)propyltrimethoxysilane and p-diphenol are added thereto, and the 3-(methacryloyloxy)propyltrimethoxysilane reacts chemically with the active groups on the surface of the inorganic substrate through stirring reaction, thereby modifying the inorganic substrate. The prepared solid material is then put into toluene, and a modifier and azobisisoheptanonitrile are added thereto. Under the action of azobisisoheptanonitrile, the modifier with excellent hydrophobic properties chemically reacts with the active groups on the surface of the solid material and is finally successfully "grafted" on its surface to prepare a functional additive.

[0024] Since the prepared functional additive has nano-molybdenum sulfide as the "core" and nano-titanium dioxide as the "shell", it has excellent anti-fouling properties. Furthermore, the nano-titanium dioxide cone-thorn structure on its surface can play a good role in guiding small water droplets, reducing the accumulation of water droplets on the surface of the insulator, and can also play a certain degree of flushing of the dirt on the surface of the insulator, reducing the accumulation of dirt. In addition, with the coordinated cooperation of the embroidery ball structure and the nano-titanium dioxide cone-thorn structure, it can have a certain effect of dividing and isolating the water droplets and dirt on the surface of the insulator. The water droplets and dirt are divided into different small chambers and cannot accumulate. Since the modifier grafted on the surface of the functional additive has a good hydrophobic effect, it can effectively reduce the probability of water droplets and dirt spreading on the surface of the insulator, so that it cannot form a conductive path of a sheet-like water film on the surface of the insulator, thereby effectively avoiding the occurrence of flashover.

[0025] In summary, the insulator prepared by the present invention has excellent anti-pollution flashover performance, which effectively ensures its quality and can also prevent the probability of large-scale pollution flashover accidents during power transmission to a certain extent, thereby ensuring the safe operation of the power grid. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1: A method for preparing an anti-pollution flashover insulator, comprising the following steps:

[0028] Step 1, accurately weigh the following raw materials by weight: 50 parts of aluminum oxide, 20 parts of bauxite, 15 parts of clay, 6 parts of potassium feldspar, 3 parts of dolomite powder, 7 parts of bentonite, 15 parts of nano titanium dioxide, 4 parts of nano silicon nitride, 3 parts of sodium silicate and 2 parts of yttrium trioxide; after weighing, store and set aside;

[0029] Step 2: Put the raw materials weighed in step 1 into a sand mill for sand milling to obtain blank particles with a diameter of 3 μm; store them for future use;

[0030] Step 3, sequentially subjecting the green sheet particles obtained in step 2 to ball milling, impurity removal, moisture control, drying, green sheet repairing, baking, glazing and sintering; after naturally cooling to room temperature, coating the surface with anti-pollution flashover coating, and obtaining the anti-pollution flashover insulator after drying.

[0031] The anti-pollution flashover coating is composed of the following raw materials in parts by weight: 50 parts of epoxy resin, 7 parts of 4,4'-sulfonyl diphenylamine, 5 parts of nano magnesium hydroxide, 2 parts of nano zinc oxide, 2 parts of 1,3-cyclohexanedimethylamine, 3 parts of 1,4-butanediol diglycidyl ether and 4 parts of functional additives.

[0032] The preparation method of the functional additive comprises the following steps:

[0033] The first step is to add acrylic acid and polyethylene glycol monomethyl ether into toluene at a molar ratio of 2:1, mix and stir evenly, then add hydroquinone with a mass of 1.5% of acrylic acid and p-toluenesulfonic acid with a mass of 3% of polyethylene glycol monomethyl ether in sequence, mix and stir evenly, and reflux for 8 hours; after the reaction is completed, remove toluene and unreacted monomers in the product components, and the final product is recorded as a modifier; wherein the mass of toluene is 5 times that of polyethylene glycol monomethyl ether, and the molecular weight of polyethylene glycol monomethyl ether is 1000;

[0034] Step 2: Disperse the inorganic carrier evenly in toluene at a solid-liquid ratio of 10 g / L, then add 3-(methacryloyloxy)propyltrimethoxysilane and hydroquinone in an amount of 0.8 times the mass of the inorganic carrier, respectively, and stir evenly, and react at 80°C for 25 hours. After the reaction is completed, centrifuge, wash and vacuum dry the components of the product in turn, and store the obtained solid material for later use;

[0035] The third step is to put the solid material into toluene at a solid-liquid ratio of 20g / L, and then add a modifier with a mass of 0.3 times that of the solid material and azobisisoheptanenitrile with a mass of 0.02 times that of the solid material, mix and stir evenly, and then stir and react at a temperature of 90°C for 8h; after the reaction is completed, centrifuge, wash and vacuum dry the product components in turn, and the final product is a functional additive.

[0036] The preparation method of the inorganic carrier is as follows: nano-molybdenum sulfide is uniformly dispersed in an ethanol aqueous solution with a concentration of 70wt% at a solid-liquid ratio of 5g / L, ammonia water is added and ultrasonically dispersed uniformly, and then magnetic stirring is performed at a temperature of 45°C for 2h, and then an ethanol solution of tetrabutyl titanate is slowly added to the obtained mixed components, and the mixture is kept warm for reaction at a temperature of 50°C for 3h; after the reaction is completed, the resultant components are centrifuged, and the obtained filter cake is washed twice with anhydrous ethanol and deionized water respectively, and then vacuum dried to obtain the inorganic carrier;

[0037] Among them, the concentration of ammonia water is 25wt%, and its usage is 10% of the volume of the ethanol aqueous solution; the concentration of tetrabutyl titanate in the ethanol solution of tetrabutyl titanate is 0.08mol / L, and its usage is 60% of the volume of the mixed components.

[0038] The preparation method of nano molybdenum sulfide comprises the following steps: adding sodium molybdate and oxalic acid in an amount 0.4 times the mass of thioacetamide and 3 times the mass of thioacetamide respectively to a 2wt% thioacetamide aqueous solution, transferring the solution into a reaction kettle after magnetic stirring for 20 minutes, and sealing and heat-insulating the reaction kettle at a temperature of 180°C for 20 hours; after the reaction is completed, naturally cooling the obtained product components to room temperature, and then performing solid-liquid separation on the obtained product components, ultrasonically washing the filter cakes with anhydrous ethanol and deionized water respectively until the upper layer solution is almost colorless, and then vacuum drying the obtained solid filter material at a temperature of 60°C, and finally rapidly annealing under argon protection to obtain nano molybdenum sulfide; wherein the rapid annealing temperature is 550°C, and the annealing time is 40 minutes.

[0039] Embodiment 2: The preparation method of a pollution flashover-proof insulator provided in this embodiment is basically the same as that in Embodiment 1, except that the specific composition of the pollution flashover-proof coating and the preparation method of the functional additive used in the two embodiments are not completely the same. The specific composition of the pollution flashover-proof coating and the preparation method of the functional additive in this embodiment are as follows:

[0040] The anti-pollution flashover coating is composed of the following raw materials in parts by weight: 55 parts of epoxy resin, 8 parts of 4,4'-sulfonyl diphenylamine, 6 parts of nano magnesium hydroxide, 3 parts of nano zinc oxide, 3 parts of 1,3-cyclohexanedimethylamine, 4 parts of 1,4-butanediol diglycidyl ether and 5 parts of functional additives.

[0041] The preparation method of the functional additive comprises the following steps:

[0042] The first step is to add acrylic acid and polyethylene glycol monomethyl ether into toluene at a molar ratio of 3:1, mix and stir evenly, then add hydroquinone with a mass of 1.5% of acrylic acid and p-toluenesulfonic acid with a mass of 4% of polyethylene glycol monomethyl ether in sequence, mix and stir evenly, and reflux for 10 hours; after the reaction is completed, remove toluene and unreacted monomers in the product components, and the final product is recorded as a modifier; wherein the mass of toluene is 6 times that of polyethylene glycol monomethyl ether, and the molecular weight of polyethylene glycol monomethyl ether is 1000;

[0043] The second step is to uniformly disperse the inorganic carrier in toluene at a solid-liquid ratio of 20 g / L, and then add 3-(methacryloyloxy)propyltrimethoxysilane and hydroquinone in an amount of 1 times the mass of the inorganic carrier, respectively, and stir the mixture evenly, and then stir the mixture at 85°C for 30 hours. After the reaction is completed, centrifuge, wash and vacuum dry the components of the product in turn, and store the obtained solid material for later use;

[0044] The third step is to put the solid material into toluene at a solid-liquid ratio of 30g / L, and then add a modifier with a mass of 0.4 times that of the solid material and 0.03 times that of azobisisoheptanenitrile. After mixing and stirring evenly, stir and react at 95°C for 8h. After the reaction is completed, centrifuge, wash and vacuum dry the product components in turn, and the final product is a functional additive.

[0045] The preparation method of the inorganic carrier is as follows: nano-molybdenum sulfide is uniformly dispersed in an ethanol aqueous solution with a concentration of 80wt% at a solid-liquid ratio of 10g / L, ammonia water is added and ultrasonically dispersed uniformly, and then magnetic stirring is performed at a temperature of 50°C for 3h, and then an ethanol solution of tetrabutyl titanate is slowly added to the obtained mixed components, and the mixture is kept warm for reaction at a temperature of 55°C for 4h; after the reaction is completed, the resultant components are centrifuged, and the obtained filter cake is washed with anhydrous ethanol and deionized water for 3 times respectively, and then vacuum dried to obtain the inorganic carrier;

[0046] Among them, the concentration of ammonia water is 28wt%, and its usage is 10% of the volume of the ethanol aqueous solution; the concentration of tetrabutyl titanate in the ethanol solution of tetrabutyl titanate is 0.12mol / L, and its usage is 50% of the volume of the mixed components.

[0047] The preparation method of nano molybdenum sulfide comprises the following steps: adding sodium molybdate and oxalic acid in an amount 0.5 times the mass of thioacetamide and 4 times the mass of thioacetamide respectively to a 3wt% thioacetamide aqueous solution, transferring the mixture into a reaction kettle after magnetic stirring for 25 minutes, and sealing and heat-insulating the mixture at a temperature of 200°C for 25 hours; after the reaction is completed, naturally cooling the obtained product components to room temperature, and then subjecting the obtained components to solid-liquid separation, ultrasonically washing the filter cakes with anhydrous ethanol and deionized water respectively until the upper layer solution is almost colorless, vacuum drying the obtained solid filter material at a temperature of 65°C, and finally rapidly annealing the mixture under argon protection to obtain nano molybdenum sulfide; wherein the rapid annealing temperature is 600°C and the annealing time is 50 minutes.

[0048] Embodiment 3: The preparation method of a pollution flashover-proof insulator provided in this embodiment is basically the same as that in Embodiment 1, except that the specific composition of the pollution flashover-proof coating and the preparation method of the functional additive used in the two embodiments are not completely the same. The specific composition of the pollution flashover-proof coating and the preparation method of the functional additive in this embodiment are as follows:

[0049] The anti-pollution flashover coating is composed of the following raw materials in parts by weight: 60 parts of epoxy resin, 10 parts of 4,4'-sulfonyl diphenylamine, 8 parts of nano magnesium hydroxide, 4 parts of nano zinc oxide, 5 parts of 1,3-cyclohexanedimethylamine, 5 parts of 1,4-butanediol diglycidyl ether and 6 parts of functional additives.

[0050] The preparation method of the functional additive comprises the following steps:

[0051] The first step is to add acrylic acid and polyethylene glycol monomethyl ether into toluene at a molar ratio of 3:1, mix and stir evenly, then add hydroquinone with a mass of 2.0% of acrylic acid and p-toluenesulfonic acid with a mass of 4% of polyethylene glycol monomethyl ether in sequence, mix and stir evenly, and reflux for 12 hours; after the reaction is completed, remove toluene and unreacted monomers in the product components, and the final product is recorded as a modifier; wherein the mass of toluene is 8 times that of polyethylene glycol monomethyl ether, and the molecular weight of polyethylene glycol monomethyl ether is 1000;

[0052] Step 2: Disperse the inorganic carrier evenly in toluene at a solid-liquid ratio of 30 g / L, then add 3-(methacryloyloxy)propyltrimethoxysilane (1.2 times the mass of the inorganic carrier) and hydroquinone (0.06 times the mass of the inorganic carrier), mix and stir evenly, and react at 90°C for 40 hours. After the reaction is completed, centrifuge, wash and vacuum dry the components of the product in turn, and store the obtained solid material for future use;

[0053] The third step is to put the solid material into toluene at a solid-liquid ratio of 40g / L, and then add a modifier with a mass of 0.5 times that of the solid material and 0.03 times that of azobisisoheptanenitrile. After mixing and stirring evenly, stir and react at 95°C for 10 hours. After the reaction is completed, centrifuge, wash and vacuum dry the product components in turn, and the final product is a functional additive.

[0054] The preparation method of the inorganic carrier is as follows: nano-molybdenum sulfide is uniformly dispersed in an ethanol aqueous solution with a concentration of 85wt% at a solid-liquid ratio of 10g / L, ammonia water is added and ultrasonically dispersed uniformly, and then magnetic stirring is performed at a temperature of 55°C for 3h, and then an ethanol solution of tetrabutyl titanate is slowly added to the obtained mixed components, and the mixture is kept warm for reaction at a temperature of 60°C for 5h; after the reaction is completed, the resultant components are centrifuged, and the obtained filter cake is washed with anhydrous ethanol and deionized water for 3 times respectively, and then vacuum dried to obtain the inorganic carrier;

[0055] Among them, the concentration of ammonia water is 28wt%, and its usage is 10% of the volume of the ethanol aqueous solution; the concentration of tetrabutyl titanate in the ethanol solution of tetrabutyl titanate is 0.12mol / L, and its usage is 60% of the volume of the mixed components.

[0056] The preparation method of nano molybdenum sulfide comprises the following steps: adding sodium molybdate and oxalic acid in an amount 0.6 times the mass of thioacetamide and 5 times the mass of thioacetamide respectively to a 5wt% thioacetamide aqueous solution, transferring the solution into a reaction kettle after magnetic stirring for 30 minutes, and sealing and heat-insulating the reaction kettle at a temperature of 220°C for 25 hours; after the reaction is completed, naturally cooling the obtained product components to room temperature, and then performing solid-liquid separation on the obtained product components, ultrasonically washing the filter cakes with anhydrous ethanol and deionized water respectively until the upper solution is almost colorless, vacuum drying the obtained solid filter material at a temperature of 70°C, and finally rapidly annealing under argon protection to obtain nano molybdenum sulfide; wherein the rapid annealing temperature is 650°C and the annealing time is 60 minutes.

[0057] Comparative Example 1 is different from Example 1 in that an equal amount of an inorganic carrier is used to replace the functional auxiliary agent in this comparative example.

[0058] The difference between Comparative Example 2 and Example 1 is that an equal amount of nano-molybdenum sulfide is used to replace the functional additive in this comparative example.

[0059] Performance test: The relevant performances of the anti-pollution flashover insulator samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 were tested as follows:

[0060] 1. Photocatalytic degradation rate: Each group of anti-pollution flashover insulator samples were added into 100mL methyl orange solution (40mg / L) for photocatalytic degradation experiment. The visible light intensity at the surface of the solution was 10mW / cm 2During the degradation process, samples were taken every 30 minutes, and 5 mL was sampled each time. The absorbance was measured by TU-1901 UV-visible spectrophotometer to analyze the change in methyl orange concentration. The photocatalytic degradation rate was then calculated based on the change in absorbance. The photocatalytic degradation time was 2 hours.

[0061] 2. Artificial simulation of pollution accumulation: Experiments were carried out in the artificial pollution accumulation test system of the State Grid UHV AC test base. Specifically, 50μm sodium chloride and diatomaceous earth were used to simulate pollution. The rain rate was 1.0mm / min, and the rain lasted for 10 minutes; artificial spraying lasted for 15 minutes and drying for 60 minutes. The samples were operated in this environment for 5 days to observe the pollution accumulation on the surface of each group of anti-pollution flashover insulator samples.

[0062] 3. Flashover test: Sodium chloride, diatomaceous earth with a particle size of 2000 mesh, and water are mixed evenly in a mass ratio of 1:5:15 by ball milling, and each group of anti-pollution flashover insulator samples are evenly smeared by quantitative brushing, and then the samples are wetted in an artificial ultrasonic fog test box built in the laboratory. The water used in the test is deionized water with a conductivity of 12.68μS / cm. The test power supply is a 600kV / 0.5A thyristor double feedback double voltage rectifier DC test power supply. When the leakage current is 0.5A, its dynamic voltage drop is less than 5%, and the ripple factor of the voltage during flashover is less than 3%, which meets the IEC standard and national standard and the power supply requirements for DC pollution test. The electrode uses a cylindrical electrode. The test steps are as follows: Place the anti-pollution flashover insulator samples of each group after smearing horizontally in the artificial ultrasonic fog test box, turn on the ultrasonic fog generator, and use 15.86mL / (m 3 ·min) of atomization volume is continuously supplied, and the high-voltage power supply is turned on. A DC voltage of 200 kV is applied between the two circular electrodes, that is, wetting under a DC electric field, for 10 min. The voltage is increased uniformly at a rate of 5 kV / s until flashover occurs on the surface of the anti-pollution flashover insulator sample. The flashover voltage, that is, the highest voltage value occurring during the pressurization process, is recorded. The test is repeated 3 times for each sample and the average value is taken.

[0063] The test data obtained above are recorded in Table 1:

[0064] Table 1

[0065]

[0066] By comparing and analyzing the relevant data in Table 1, it can be seen that the prepared insulator has excellent anti-pollution flashover performance, which effectively ensures its quality and can also prevent the probability of large-scale pollution flashover accidents during power transmission to a certain extent, thereby ensuring the safe operation of the power grid. This shows that the anti-pollution flashover insulator and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0067] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0068] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing an anti-pollution flashover insulator, characterized in that: The following steps are involved: Step 1, accurately weigh the following raw materials in parts by weight: 50-55 parts of aluminum oxide, 20-30 parts of bauxite, 15-20 parts of clay, 6-10 parts of potassium feldspar, 3-6 parts of dolomite powder, 7-10 parts of bentonite, 15-25 parts of nano titanium dioxide, 4-6 parts of nano silicon nitride, 3-5 parts of sodium silicate and 2-3 parts of rare earth oxide; after weighing, store and set aside; Step 2: Put the raw materials weighed in step 1 into a sand mill for sand milling to obtain blank particles with a diameter of 3 to 5 μm; store them for future use; Step 3, sequentially subjecting the blank particles obtained in step 2 to ball milling, impurity removal, moisture control, drying, blank repair, baking, glazing and sintering; after naturally cooling to room temperature, coating the surface with anti-pollution flashover coating, and obtaining the anti-pollution flashover insulator after drying; The anti-pollution flashover coating is composed of the following raw materials in parts by weight: 50-60 parts of epoxy resin, 7-10 parts of 4,4'-sulfonyl diphenylamine, 5-8 parts of nano magnesium hydroxide, 2-4 parts of nano zinc oxide, 2-5 parts of 1,3-cyclohexanedimethylamine, 3-5 parts of 1,4-butanediol diglycidyl ether and 4-6 parts of functional additives; The preparation method of the functional additive comprises the following steps: The first step is to add acrylic acid and polyethylene glycol monomethyl ether into toluene at a molar ratio of 2 to 3:1, mix and stir evenly, then add hydroquinone with a mass of 1.5 to 2.0% of acrylic acid and p-toluenesulfonic acid with a mass of 3 to 4% of polyethylene glycol monomethyl ether in sequence, mix and stir evenly, and reflux for 8 to 12 hours; after the reaction is completed, remove toluene and unreacted monomers in the product components, and the final product is recorded as a modifier; wherein the mass of toluene is 5 to 8 times that of polyethylene glycol monomethyl ether, and the molecular weight of polyethylene glycol monomethyl ether is 1000; Step 2: Disperse the inorganic carrier evenly in toluene at a solid-liquid ratio of 10 to 30 g / L, then add 3-(methacryloyloxy)propyltrimethoxysilane and hydroquinone in an amount of 0.8 to 1.2 times the mass of the inorganic carrier, respectively, and stir evenly, and stir the mixture at a temperature of 80 to 90° C. for 25 to 40 hours. After the reaction is completed, centrifuge, wash, and vacuum dry the resulting components in turn, and store the resulting solid material for later use. The third step is to put the solid material into toluene at a solid-liquid ratio of 20 to 40 g / L, and then add a modifier of 0.3 to 0.5 times the mass of the solid material and 0.02 to 0.03 times the mass of azobisisoheptanenitrile, mix and stir evenly, and react at a temperature of 90 to 95° C. for 8 to 10 hours; after the reaction is completed, centrifuge, wash and vacuum dry the resultant components in turn, and the final product is a functional additive; The preparation method of the inorganic carrier is as follows: nano-molybdenum sulfide is uniformly dispersed in an ethanol aqueous solution with a concentration of 70-85wt% at a solid-liquid ratio of 5-10g / L, ammonia water is added and ultrasonically dispersed uniformly, and then magnetic stirring is performed at a temperature of 45-55°C for 2-3h, and then an ethanol solution of tetrabutyl titanate is slowly added to the obtained mixed component, and the mixture is kept warm for reaction at a temperature of 50-60°C for 3-5h; after the reaction is completed, the resultant components are centrifuged, and the obtained filter cake is washed with anhydrous ethanol and deionized water for 2-3 times, and then vacuum dried to obtain the inorganic carrier; the concentration of tetrabutyl titanate in the ethanol solution of tetrabutyl titanate is 0.08-0.12mol / L, and the amount thereof is 40-60% of the volume of the mixed component; The preparation method of nano molybdenum sulfide comprises the following steps: adding sodium molybdate and oxalic acid in an amount of 0.4 to 0.6 times the mass of thioacetamide to a 2 to 5 wt % thioacetamide aqueous solution, respectively, transferring the solution into a reaction kettle after magnetic stirring for 20 to 30 minutes, and sealing and heat-insulating the reaction kettle at a temperature of 180 to 220° C. for 20 to 25 hours; after the reaction is completed, naturally cooling the obtained product components to room temperature, and then performing solid-liquid separation on the obtained product components, ultrasonically washing the filter cakes with anhydrous ethanol and deionized water respectively until the upper layer solution is almost colorless, and then vacuum drying the obtained solid filter material at a temperature of 60 to 70° C., and finally rapidly annealing under argon protection to obtain nano molybdenum sulfide.

2. The method for preparing a pollution-proof flashover insulator according to claim 1, characterized in that: The rapid annealing temperature is 550-650° C., and the annealing time is 40-60 min.

3. The method for preparing a pollution flashover-proof insulator according to claim 1, characterized in that: The rare earth oxide is selected from any one of yttrium trioxide, lanthanum trioxide and samarium trioxide.

4. The method for preparing a pollution-flashover-proof insulator according to claim 1, characterized in that: The concentration of the ammonia water is 25-28 wt %, and the amount thereof is 5-10% of the volume of the ethanol aqueous solution. 5.An anti-pollution flashover insulator, characterized in that: The anti-pollution flashover insulator is prepared by the preparation method of any one of claims 1 to 4.

Citation Information

Patent Citations

  • A high-strength, impact-resistant porcelain insulator and its preparation method

    CN108840660B

  • Molybdenum disulfide nano-hydrangea structural semiconductor material and preparation method thereof

    CN104556230A

  • Method for preparing flower-shaped MoS2 / TiO2 photocatalytic material

    CN110180561A

  • High-flowability high-performance concrete with low cementing material content, and preparation method thereof

    CN112430042A

  • Low-temperature-resistant high-voltage power transmission porcelain insulator and preparation method thereof

    CN112441824A